Magneto micro-polar flow considering weak concentration over a vertical porous surface in the presence of viscous dissipation and Ohmic heating: effects of Hall and ion-slip currents. (16th October 2012) - Jahan, Esrat; Ferdows, M.; Hamad, M.A.A.; Postelnicu, Adrian
The present paper dealing with the effects of Hall and ion-slip currents on the flow of a steady, viscous, incompressible, electrically conducting micro-polar fluid past a vertical plate in a saturated porous medium has been studied for the case of a weak concentration. The effects of viscous dissipation and Ohmic heating are incorporated in the energy equation. Governing partial differential equations are reduced to a system of ordinary differential equations by the usual method of similarity transformation and then solved numerically with the Nachtsheim-Swigert shooting iteration technique based on the Runge-Kutta sixth order iteration scheme. The expressions for the non-dimensional velocity, angular velocity and temperature profiles are shown graphically for different values of the Prandtl number Pr, micro-polar parameter Δ, Grashof number Gr, permeability parameter K 2, magnetic field parameter M, Hall parameter β e, ion-slip parameter β i and micro-rotational parameter λ. Further, the effects of the problem parameters on skin friction coefficients due to primary and secondary velocity, local couple stress and the local Nusselt number are constructed graphically. Comparisons with previous published works are performed and the results are found to be in favourable agreement.